Strategi Pembelajaran Bahasa Arab melalui Pendekatan Bermain dan Bernyanyi pada Anak Usia Dini di TK Dharma Wanita - Nurul Fitria Aprilia; Giska Enny Fauziah (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
Arabic language learning for early childhood requires strategies that are appropriate for their developmental characteristics, namely learning through play in a fun atmosphere. This study was motivated by the importance of mastering basic Arabic from an early age as a foundation for religious learning and simple communication. The research question is how Arabic language learning strategies through play and singing approaches can be applied at Dharma Wanita Kindergarten. The purpose of this study is to describe the application of play and singing-based Arabic language learning strategies and to determine their impact on children's motivation and understanding. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the application of play and singing strategies can increase enthusiasm, active involvement, and memory of Arabic vocabulary in early childhood, so that learning is more effective, enjoyable, and appropriate for their stage of development.